2021
DOI: 10.3390/bioengineering8090125
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Methodologies to Produce Capped Mesoporous Silica with Hydroxyapatite and the Influence in Intracellular Signaling as Cytotoxicity on Human Umbilical Vein Endothelial Cells

Abstract: Mesoporous silica has unique properties such as controllable mesoporous structure and size, good biocompatibility, high specific surface area, and large pore volume. For that reason, this material has been broadly functionalized for biomedical applications, such as optical imaging, magnetic resonance imaging (MRI), positron emission tomography (PET), computed tomography (CT), ultrasound imaging, and widely employed as drug delivery systems. In this study, we synthesized fiber-type mesoporous silica capped with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…However, this effect did not apply to RVS. Finally, Barros et al, showed that adding hydroxyapatite to mesoporous silica had no meaningful influence on HUVEC cell viability [ 57 ]. However, this study shows that the CS and DX layers not only have no toxicity to the cardiovascular system but also help decrease toxicity and increase biocompatibility.”
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…However, this effect did not apply to RVS. Finally, Barros et al, showed that adding hydroxyapatite to mesoporous silica had no meaningful influence on HUVEC cell viability [ 57 ]. However, this study shows that the CS and DX layers not only have no toxicity to the cardiovascular system but also help decrease toxicity and increase biocompatibility.”
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This is corroborated by Assis et al [ 72 ] that using Ag nanoparticles/α-Ag2WO4 demonstrated that they are safe for use after assay with FGH cells. Also, Silva de Barros et al [ 73 ] demonstrated that capped mesoporous silica with hydroxyapatite is secure after evaluation with FGH cells.…”
Section: Discussionmentioning
confidence: 99%
“…These systems can be targeted to the tumor site, increasing bioavailability and allowing the transportation of multiple drugs or molecules to the tumor [ 13 ]. Active targeting strategies, achieved by reducing particle size or modifying the particle surface with hydrophilic polymers, as well as by conjugating passive and specific ligands to the particle surface, are effective methods employed with nanosized drug delivery systems [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%